2010
DOI: 10.4088/jcp.09m05845gre
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Anxiety in Children and Adolescents With Bipolar Spectrum Disorders

Abstract: Objective Anxiety disorders are among the most common comorbid conditions in youth with bipolar disorder (BP). We aimed to examine the prevalence and correlates of comorbid anxiety disorders among youth with BP. Methods As part of the Course and Outcome of Bipolar Youth study (COBY), 446 youth ages 7 to 17, who met DSM-IV criteria for BP-I (n=260), BP-II (n=32) or operationalized criteria for BP not otherwise specified (BP-NOS; n=154) were included. Subjects were evaluated for current and lifetime Axis-I psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 69 publications
2
52
1
2
Order By: Relevance
“…In the COBY study, 44% of youth had at least one lifetime anxiety disorder, and nearly 20% had two or more, with the most prevalent being separation anxiety (24%) and generalized anxiety disorder (GAD) (16%) (234). A family history study that included 157 patients (age 6-17 years) with BD I revealed extremely high rates of comorbid attention-deficit hyperactivity disorder (ADHD) (85%), oppositional defiant disorder (90%), two or more anxiety disorders (64%), conduct disorder (51%), and SUD (12%) (235).…”
Section: Comorbidities and Mimicsmentioning
confidence: 99%
“…In the COBY study, 44% of youth had at least one lifetime anxiety disorder, and nearly 20% had two or more, with the most prevalent being separation anxiety (24%) and generalized anxiety disorder (GAD) (16%) (234). A family history study that included 157 patients (age 6-17 years) with BD I revealed extremely high rates of comorbid attention-deficit hyperactivity disorder (ADHD) (85%), oppositional defiant disorder (90%), two or more anxiety disorders (64%), conduct disorder (51%), and SUD (12%) (235).…”
Section: Comorbidities and Mimicsmentioning
confidence: 99%
“…Despite BD may frequently manifest in broad phenotype among young subjects, majority of the subjects in this study had DSM-IV-defined BD type I or II. However it may be important to note that many studies on pediatric BD that were cited in this paper have also included subjects with a diagnosis of BD-NOS (15,19,30). This study may have several limitations.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Furthermore, nearly half of the adult or young subjects with a diagnosis of BD have reported depressive episodes before their diagnosis of BD (3,4,(13)(14)(15). Meanwhile, young subjects with BD have been reported to have high rates of psychiatric comorbidity (3,4,(16)(17)(18)(19)(20)(21)(22). Despite comorbidity rates and patterns may change depending on the age group (children vs adolescents) and setting (clinical vs community samples), high rates of attention deficit hyperactivity disorder (ADHD) (up to 80%), oppositional defiant disorder (ODD) (up to 80%), conduct disorder (CD) (up to 37%), anxiety disorders (AD) (up to 56%), substance use disorders (SUD) (up to 40%), and obsessive compulsive disorder (OCD) (up to 40%) have been reported (16)(17)(18)(19)(20)(21)(22).…”
Section: öZetmentioning
confidence: 99%
See 1 more Smart Citation
“…Separation anxiety disorder has an association with higher rates of subsequent depression in a limited number of studies (Horn & Wuyek, 2010). Separation anxiety disorders are among the most common comorbid conditions in youth with bipolar disorder (BP) (Sala et al, 2010). A history of separation anxiety disorder is frequently reported by patients with obsessive-compulsive disorder (Mroczkowski et al, 2011).…”
Section: Comorbiditymentioning
confidence: 99%